Influence of La2O3 Addition on CuO/CeO2 Catalysts for the Water-Gas Shift Reaction - de Freitas Silva, Tatiana; Assaf, José Mansur; Lucrédio, Alessandra Fonseca [UNESP]; Reis, Cristhiane Guimarães Maciel; Almeida, Karina Arruda (American Chemical Society (ACS), 2025)
CuO/CeO2 and CuO/xCeO2-yLa2O3 catalysts, synthesized with varying CeO2 and La2O3 molar ratios (1:1, 1:2, and 2:1), were prepared via the hydrothermal method and tested in the water-gas shift reaction (150-350 °C). La2O3 addition altered structural properties, reducing surface area and copper dispersion. XANES and in situ XRD confirmed metallic Cu species during reduction and reaction. Catalytic tests revealed CuO/CeO2 excelled at low temperatures, while La2O3-doped catalysts, especially CuO/1CeO2-1 La2O3, performed better at 250-350 °C. Stability tests showed La2O3-doped catalysts resisted deactivation and sintering better than CuO/CeO2, even with CO2 and H2 in the feed.